COMPETENCE, ORGANIZATIONAL CULTURE, WORK TEAM TO HUMAN CAPITAL RESOURCES MANAGEMENT DIRECTORATE - Adhi Widyakto; Lulus Prapti; Kamalina Din Jannah (Fakultas Ekonomi Universitas Pekalongan, 2021)
This research about the human capital approach to manage human resources becoming productive. The method used is descriptive and causality. The statistical test in this study uses Multiple Regression Analysis. Based on observations in Indonesia, there are still many companies doesn’t have implemented the most optimal approach to human capital. The results of study indicate that the human capital component hasn’t been optimal, especially in terms of individual capability and individual motivation. The purpose of study was determining the effect of several variables such as competence, organizational culture and work team on employee’s performance. The method used is descriptive and causality. The statistical test in this study uses Multiple Regression Analysis. Respondents involved in this study were 93 employees who were permanent employees at the Human Resources and Facility Management Directorate at PT Telecommunication Indonesia, Jakarta Head Office. The sampling method of his research using purposive sampling. Data accumulation techniques using questionnaires with closed answer model. Data analysis was performed using multiple regression. The results indicates that partially competence has an effect on employee’s performance, The Organization Climate doesn’t affect employee’s performance, work Group Efficiency affects employee’s performance.